2017
DOI: 10.1007/s00467-017-3614-7
|View full text |Cite
|
Sign up to set email alerts
|

Posterior urethral valve in fetuses: evidence for the role of inflammatory molecules

Abstract: This study shows that inflammatory molecules are already increased in fetuses with PUV at the mean gestational age of 22 weeks, suggesting a physiopathological role for inflammation just after the embryological formation of the urethral membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Another important finding of the present study is the significant elevation of serum IL‐10 in CAKUT patients, compared to unaffected children. Previous study has shown that urinary level of IL‐10 was significantly higher in samples obtained from foetuses with PUV in comparison to healthy preterm neonates . In addition, we have detected some extremely high IL‐10 levels in cases with severe parenchymal damage.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Another important finding of the present study is the significant elevation of serum IL‐10 in CAKUT patients, compared to unaffected children. Previous study has shown that urinary level of IL‐10 was significantly higher in samples obtained from foetuses with PUV in comparison to healthy preterm neonates . In addition, we have detected some extremely high IL‐10 levels in cases with severe parenchymal damage.…”
Section: Discussionsupporting
confidence: 50%
“…Previous study has shown that urinary level of IL-10 was significantly higher in samples obtained from foetuses with PUV in comparison to healthy preterm neonates. 25 In addition, we have detected some extremely high IL-10 levels in cases with severe parenchymal damage. Bearing in mind the functional role of IL10-1082A/G polymorphism, we hypothesized that the observed inter-individual differences could be due to a current -1082A/G-genotype.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…As we know from experimental data, LUTO fetuses present increased urinary levels of RAS molecules like angiotensin (Ang) I, Ang‐(1‐7), and angiotensin‐converting enzyme 2 in comparison with controls . This may be a regulatory response to an inflammatory process, which is triggered by LUTO . Chowdhury et al demonstrated that serum prorenin was higher in LUTO cases than in controls and declined after corrective surgery .…”
Section: Discussionmentioning
confidence: 99%